Issues of compensation for negative amounts of value added tax to taxpayers - Erkayev Nodir Xudayberdiyevich (Genius Journals, 2025)
Studying the administration of value-added tax in our country is also related to the improvement of value-added tax. The article analyzes the specific features of calculating the value-added tax base, some complications and problems in its determination, and focuses on issues of improving the formation of the tax base. In addition, based on the results of the changes and additions made in determining and calculating the value-added tax base, appropriate conclusions were formed and recommendations were developed.
Keywords: Value added; value added tax; budget policy